Feminism for the Americas : the making of an international human rights movement - Marino, Katherine M. (Gender & American culture., 2019)
This book reveals the story of six dynamic women who drove Pan-American feminism from the 1920s-1940s: Uruguayan Paulina Luisi, Brazilian Bertha Lutz, Chilean Marta Vergara, Cuban Ofelia Dominguez Navarro, Panamanian Clara Gonzalez, and U.S. citizen Doris Stevens. The deep friendships and intense rivalries among these women during an era marked by imperialism, racism, and fascism gave rise to a feminism sensitive to multiple forms of oppression. This advocacy sped changes for women throughout the Americas--suffrage, equal nationality rights, rights to hold public office, equal pay for equal work, and maternity legislation. But just as importantly, these six leaders were forerunners in understanding the complexity of power relations in international affairs, and they used their expertise to not only shape the trajectory of international women's rights but include human rights as defined and established in the United Nations Charter. --